Foods of Chile - Sheen, Barbara; Gale Group (Detroit, Mich. KidHaven Press, 2011)
Explores the foods, cooking traditions, customs, eating habits, and food sources of Chile. Topics include favorite dishes, snacks and sweets, traditional holiday meals, and the preparations and traditions associated with these foods.
Ch 1. A land of plenty -- ch 2. A cultural exchange -- ch 3. Tea time -- ch 4. Holidays and fiestas.
Electronic reproduction.
Keywords: Cooking, Chilean; Electronic books; Cookbooks